Identification of cost data input in life cycle cost (LCC) for building projects - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2014)
Life Cycle Cost (LCC) is an economic assessment technique that produces outputs, which will give useful cost information to many including clients, estimators and researchers in facilitating them to make better decision in the process of determining the most optimum total costs of an asset, such as a building, over an anticipated life or in comparing the most cost-effective of mutually exclusive alternatives. Past studies have confirmed that quality, currency and adequacy of cost data used as inputs as well as the method used for the LCC analysis are of paramount importance in effort to produce reliable LCC outputs. There are different kinds of data to be used as inputs in LCC analysis and the type of data to be used is contingent upon the intended output of the LCC analysis. In the current research the focus is on cost data inputs for buildings’ LCC. The objective of the poster is to present the outcome of a study to identify the types of cost data as inputs requirements for a comprehensive LCC estimation for building works in the Malaysian construction industry. The study being reported herein is drawn from a three-year programme of research to purposely enhance the quality of LCC outputs for building projects in Malaysia. The methodology employed for the study comprised comprehensive review of related literature and three rounds of modified Delphi. The participants that completed all three rounds of modified Delphi questionnaire were 20 experts on LCC in Malaysia. The key findings of the study include that in the context of Malaysia (i) the major hurdle of conducting LCC analysis is somewhat homogeneous: lack of reliable, accurate, and current cost data inputs; (ii) quality of data input requirements for producing reliable LCC outputs should possess the following characteristics: availability, accessibility, currency and reliability of cost data; (iii) a total of 35 types of cost data requirements for producing reliable LCC outputs that are available and accessible have been identified; and (iv) 5 formulas have been identified that could be employed to facilitate the LCC estimators to update the historical data for producing reliable LCC outputs. The outcome of the study is considered significant in effort to assist clients, estimators and researchers to make better decision in terms of determining the most optimum total costs of an asset and to help reject the common belief that cost of an asset only comprised of the capital costs and that the lowest capital cost is the best.